2016
DOI: 10.1038/ncomms10312
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous beating rate adaptation in human stem cell-derived cardiomyocytes

Abstract: The therapeutic success of human stem cell-derived cardiomyocytes critically depends on their ability to respond to and integrate with the surrounding electromechanical environment. Currently, the immaturity of human cardiomyocytes derived from stem cells limits their utility for regenerative medicine and biological research. We hypothesize that biomimetic electrical signals regulate the intrinsic beating properties of cardiomyocytes. Here we show that electrical conditioning of human stem cell-derived cardiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
141
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(162 citation statements)
references
References 70 publications
14
141
1
6
Order By: Relevance
“…This suggested that the developing stage ratio provided a favorable microenvironment for hiPSC-CM development and supported the developmental basis for cardiac organoid fabrication. This finding is consistent with previous engineered findings showing that cardiac constructs containing a majority of cardiomyocytes of the construct supports increased hiPSC-CM functions (15, 17, 22, 48). The developing stage cell ratio for cardiac organoids was used for the remainder of the experiments.…”
Section: Resultssupporting
confidence: 93%
“…This suggested that the developing stage ratio provided a favorable microenvironment for hiPSC-CM development and supported the developmental basis for cardiac organoid fabrication. This finding is consistent with previous engineered findings showing that cardiac constructs containing a majority of cardiomyocytes of the construct supports increased hiPSC-CM functions (15, 17, 22, 48). The developing stage cell ratio for cardiac organoids was used for the remainder of the experiments.…”
Section: Resultssupporting
confidence: 93%
“…The ultrastructural machinery for contraction/relaxation was confirmed by the positioning of t-tubules in proximity to cardiac calcium pump SERCA2A/ ATP2A2 and sodium-calcium exchanger NCX1/ SLC8A1 . Consistently, transcription of the genes responsible for clearing cytosolic calcium ( ATP2A2 and SLC8A1 17 ) increased over time and the sequestration and extrusion of calcium became faster, enabling the iPS-CMs to relax and respond to contractile triggers. Blocking Ca V 1.2 by nifedipine or verapamil gradually reduced calcium transients in a training-dependent manner, while the response to caffeine indicated that only the early/intensity tissues had functional intracellular calcium stores.…”
mentioning
confidence: 88%
“…Human iPS-CMs can be matured by long-term culture, electrical, hydrodynamic and mechanical stimulation 8,9,1517,31 . Recent studies indicate that the in vitro culture may not follow the developmental paradigm: high stimulation frequencies benefit maturation in vitro 9 , while the native heart beats more slowly following birth 5,13 .…”
mentioning
confidence: 99%
“…An alternative strategy for cardiac maturation is electrical stimulation, which was shown to improve calcium handling and electrophysiological properties of iPSC-CMs (10) and to regulate their beating rate (11). However, the evidence that mechanical and/or electrical stimulation can lead to ultrastructural and functional hallmarks of adult heart muscle: sarcomeres with dense mitochondria, T-tubules and M-lines, and a positive force-frequency relationship (Bowditch phenomenon) is yet to be published.…”
Section: Tackling Tissue-engineered Heart Repairmentioning
confidence: 99%